2019
DOI: 10.3389/fphar.2019.00641
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Vancomycin Dosing in Chronic Kidney Disease by Deriving and Implementing a Web-Based Tool Using a Population Pharmacokinetics Analysis

Abstract: Background: Chronic kidney disease (CKD) patients requiring intravenous vancomycin bear considerable risks of adverse outcomes both from the infection and vancomycin therapy itself, necessitating especially precise dosing to avoid sub- and supratherapeutic vancomycin exposure. Methods: In this retrospective study, we performed a population pharmacokinetic analysis to construct a vancomycin dose prediction model for CKD patients who do not require renal replacement therapy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 42 publications
(51 reference statements)
0
16
0
1
Order By: Relevance
“…26 Truong et al 39 showed that time to goal trough attainment for the PK and traditional groups was 54.0 ± 35.4 hours and 74.4 ± 45.7 hours, respectively ( P = 0.04). In contrast, Brinkman et al 25 and Dorajoo et al 37 did not find significant difference in time to target trough concentration between the 2 groups. Loading dose was included in the individualization regimen in studies conducted by Cardile et al 26 and Brinkman et al 25…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…26 Truong et al 39 showed that time to goal trough attainment for the PK and traditional groups was 54.0 ± 35.4 hours and 74.4 ± 45.7 hours, respectively ( P = 0.04). In contrast, Brinkman et al 25 and Dorajoo et al 37 did not find significant difference in time to target trough concentration between the 2 groups. Loading dose was included in the individualization regimen in studies conducted by Cardile et al 26 and Brinkman et al 25…”
Section: Resultsmentioning
confidence: 84%
“…All the 21 studies included were published in English, of which 3 were RCTs 22-24 and 18 were cohort studies. 13,16,17,25-39 These trials included 4346 patients in all. A total of 14 studies were conducted among adults 13,16,17,22,24-26,30,32,35-39 ; 1 study was conducted in pediatrics 33 and 1 included both adults and pediatric patients, 34 whereas the remaining were in neonates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations